Dietary interventions and nutritional strategies for menopausal health: a mini review - Liu, Yi-chen; Guo, Zhi-qing (Frontiers in Nutrition, 2025)
Menopause constitutes a pivotal physiological transition characterized by irreversible cessation of ovarian function and profound estrogen depletion, precipitating vasomotor symptoms, accelerated bone resorption, heightened cardiovascular risk, and adverse metabolic reprogramming. This mini-review systematically synthesizes evidence from 42 high-quality studies (18 systematic reviews/meta-analyses and 24 randomized controlled trials) published between January 2020 and October 2025. Studies were sourced via structured searches of PubMed/MEDLINE, Scopus, Web of Science, and Cochrane Library, focusing on dietary patterns and targeted nutrient interventions in peri- and postmenopausal women (inclusion: outcomes on vasomotor symptoms, bone health, cardiovascular risk, or metabolic parameters; exclusion: hormone replacement therapy or non-human research). Narrative synthesis incorporated critical appraisal of study quality, heterogeneity, and bias. Adherence to the Mediterranean diet consistently demonstrates clinically meaningful reductions in blood pressure and triglyceride concentrations, thereby attenuating cardiovascular burden. Calcium and vitamin D co-supplementation robustly preserves bone mineral density and mitigates fracture risk. Plant-based dietary patterns rich in whole grains, fruits, and vegetables are associated with attenuated symptom severity and enhanced healthy aging trajectories. Despite these advances, postmenopausal women remain disproportionately vulnerable to micronutrient deficiencies, underscoring the imperative for balanced, nutrient-dense intake. These non-pharmacological strategies confer substantial improvements in quality of life, yet persistent gaps in long-term outcomes and representation of diverse populations necessitate further investigation.